Criterion and norm referenced tests in the education system: livening up the debate - Mashingaidze, Samuel (Midlands State University, 2016)
Any form of assessment should support purposes of learning and reflect the principles of curriculum for excellence. Curriculum policies ought to recognize the importance of assessment as an integral part of teaching and learning. Thus tests as forms of assessment are fundamental for effective teaching and learning to take place. Generally tests serve varied purposes depending on the type of test. The purposes of tests range from enabling teachers to identify their weaknesses and strengths of instruction for future adjustments to informing parents/guardians of their children s progress in learning. It is through tests only that the effectiveness of most education programmes can be determined. While tests can be classified into two categories, essay and objective tests, they can also be classified according to their purposes as norm referenced tests and criterion referenced tests. School teachers therefore need to acquaint themselves with the subject of testing, that is, learn more about testing systems, how to interpret test results, etc. It is in the thrust of this paper to present comparatively the epistemological dimensions of each of the two forms of tests.